Sliding mode fuzzy controller for the control of nonlinear systems - Z. Taha (1994)
The aim of the work described in this paper is to develop a suitable controller for positioning a pneumatic cylinder. The dynamics of a pneumatic servosystem is nonlinear because of the compressibility of air. In addition, on-off or binary valves often used in actuating pneumatic cylinders introduces a nonlinear element into the control loop. In this paper, a fuzzy logic controller based on the theory of variable structure systems is proposed. The theory of variable structure has reduced the number of rules required for fuzzy logic control. Experimental results have shown that the controller is able to overcome the nonlinearities and position a pneumatic cylinder accurately